Polyurethane Microparticles for Stimuli Response and Reduced Oxidative Degradation in Highly Porous Shape Memory Polymers - Weems, A. C. (ACS Appl Mater Interfaces, 2018)
Shape memory polymers (SMPs) have been found to be promising biomaterials for a variety of medical applications; however, the clinical translation of such technology is dependent on tailorable properties such as gravimetric changes in degradation environments. For SMPs synthesized from amino-alcohols, oxidation resulting in rapid mass loss may be problematic in terms of loss of material functionality as well as toxicity and cytocompatibility concerns. Control of gravimetric changes was achieved through the incorporation of small molecule antioxidants, either directly into the polymer matrix or included in microparticles to form a SMP composite material. With direct incorporation of small molecule phenolic antioxidant 2,2′-methylenebis(6-tert-butyl)-methylphenol (Methyl), SMPs displayed reduce strain recovery by more than 50% (Methyl) and increase elastic modulus from approximately 1.4 to 2.3 MPa, at the expense of the strain to failure being reduced from 45% to 32%. Importantly, such changes could not ensure retention of the antioxidants and therefore did not increase oxidative stability beyond 15 days in accelerated oxidative conditions (equivalent to approximately 800 days in porcine aneurysms) in all cases except for the inclusion of a hindered amine that capped network growth, which also resulted in shape memory reduction (only 80% recoverable strain achieved). However, the inclusion of antioxidants in microparticles was found to produce materials with similar thermomechanical (T(g) migration below 1.0 °C) and shape recovery of 100%, while increasing oxidative resistance compared to controls (oxidation onset was delayed by 3 days and material lifespan increased to approximately 20–22 days in accelerated oxidative solution or beyond 1000 days in the porcine aneurysm). The microparticle composite SMPs also act as a platform for environmental sensing, such as pH-dependent fluorescence shifts and payload release, as demonstrated by fluorescent dye studies using phloxine B and nile blue chloride and the release of antioxidants over a 3 week period. The use of polyurethane-urea microparticles in porous SMPs is demonstrated to increase biostability of the materials, by approximately 25%, and ultimately extend their lifespan for use in aneurysm occlusion as determined through calculated in vivo degradation rates corresponding to a porcine aneurysm environment.